Metal–organic framework thin films for protective coating of Pd-based optical hydrogen sensors - Szilagyi, Petra; Westerwaal, R.; van de Krol, R.; Geerlings, H.; Dam, B. (RSC Publishing, 2013)
For an economy with hydrogen as the major energy carrier, the development of affordable, reliable, sensitive and selective hydrogen sensors is indispensable. In principle, Pd-based optical-fibre sensors could meet such requirements if the cross-contamination effect of the Pd surface by e.g. oxygen, moisture or carbon monoxide can be prevented. Here, we propose the pioneering idea of using a metal–organic framework (MOF) thin film as a tuneable protective coating. As a proof of principle, we demonstrate that homogeneous and continuous MOF coatings can indeed be deposited on Pd surfaces without serious compromise of the sensor's response, opening the way for the optimisation of hydrogen-selective MOF thin films.